001 Multiparametric mapping to understand pathophysiology in cardiac amyloidosis. (3rd April 2017) - Kotecha, Tushar; Martinez-Naharro, Ana; Treibel, Thomas A; Francis, Rohin; Nordin, Sabrina; Abdel-Gadir, Amna; Knight, Daniel S; Zumbo, Giulia; Rosmini, Stefania; Maestrini, Viviana; Bulluck, Heerajnarain; Rakhit, Roby; et al.
Abstract : Background: The prognosis and treatment of the 2 main types of cardiac amyloidosis, immunoglobulin light chain (AL) and transthyretin (ATTR) amyloidosis are substantially influenced by cardiac involvement. ATTR amyloidosis has better prognosis than AL despite more amyloid infiltration. This paradox suggests additional mechanisms of damage in AL amyloidosis. The aim of this study was to assess the presence and ?prognostic significance of oedema in a large population of patients with cardiac amyloidosis and compare findings among those with TTR and AL types. Methods and results: 286 patients (100 with systemic AL amyloidosis (including 49 patients scanned prior to commencing chemotherapy), 163 with cardiac ATTR amyloidosis, 12 with suspected cardiac ATTR amyloidosis (grade 1 on 99m Tc-DPD) and 11 asymptomatic individuals with amyloidogenic transthyretin(TTR) mutations), and 30 healthy volunteers were recruited. All subjects underwent CMR with T1 and T2 mapping, and ECV quantification. Left ventricular(LV) mass and ECV were higher in ATTR compared to AL whilst LV ejection fraction(EF) was significantly lower(p<0.001). There was no significant difference in ECV between treated and untreated AL (Figure 1a ). T2 was increased in cardiac amyloidosis compared to healthy volunteers with the degree of elevation being the highest in untreated AL patients (T2: 56.3±4.9 ms AL untreated, 54.0 ±4.5 ms AL treated, 54.3±4.1 ms ATTR, 48.9±2.0 ms controls, p<0.05 for all except treated AL vs ATTR) (Figure 1b ). During follow up (22.8±14.7 months), 75 (28% of AL group and 25% of ATTR group) patients died. Using Cox regression models, T2 predicted death in AL amyloidosis (hazard ratio, HR, 1.48, 95% CI 1.20–1.82) and remained significant after adjusting for EF and ECV (HR 1.31, 95% CI 1.04–1.66) (Abstract 1 Figure 2 ). Conclusion: Patients with AL amyloidosis have a worse prognosis compared to ATTR despite having less cardiac amyloid infiltration. T2 was significantly higher in untreated AL amyloidosis consistent with oedema, and was an independent predictor of prognosis. The higher ECV in ATTR was consistent with higher amyloid infiltration. These findings highlight the unique role of CMR with multiparametric mapping for characterising the cardiac effects of systemic amyloidosis and risk stratification in this population.